Crossing boundaries : work and industrial relations in perspective - Lansbury, Russell D. (New York, NY : Routledge, 2021)
"This book provides insights into the development in work, organisations and employment relations in the last 50 years. In a semi-autobiographical approach, Lansbury reflects on important contributions by other scholars, practitioners, and policy makers to work and employment relations"--
OCLC-licensed vendor bibliographic record.
Keywords: Industrial relations -- History -- 20th century; Industrial relations -- History -- 21st century; Work -- History -- 20th century; Work -- History -- 21st century; BUSINESS & ECONOMICS / General; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Workplace Culture